2014
DOI: 10.1590/s0100-69912014000300003
|View full text |Cite
|
Sign up to set email alerts
|

The cost of excessive postoperative use of antimicrobials: the context of a public hospital

Abstract: ABSTRACT ABSTRACT ABSTRACTObjective Objective Objective Objective Objective: To evaluate the improper use of antimicrobials during the postoperative period and its economic impact. Methods Methods Methods Methods Methods: We conducted a prospective cohort study by collecting data from medical records of 237 patients operated on between 01/ 11/08 and 31/12/08. Results Results ResultsResults Results: from the 237 patients with the information collected, 217 (91.56%) received antimicrobials. During the postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
(12 reference statements)
0
8
0
3
Order By: Relevance
“…The adherence of the studies with this outcome was not considered satisfactory and is not consistent with authors that claim that a more prolonged administration of prophylactic antibiotics did not favor the prevention of surgical wound infection, and may encourage the development of microbial resistance, in addition to being costly to patients, increasing the direct costs of care. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…The adherence of the studies with this outcome was not considered satisfactory and is not consistent with authors that claim that a more prolonged administration of prophylactic antibiotics did not favor the prevention of surgical wound infection, and may encourage the development of microbial resistance, in addition to being costly to patients, increasing the direct costs of care. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Due to proper antimicrobial prophylaxis, the incidence of SSIs has been reduced by 50% in some procedures and proper SAP is now considered the most important preventive measure against SSIs [7]. However, the literature suggests inappropriate SAP practice regarding the prescription, timing, and duration of antibiotic use worldwide, which prolongs the hospital stay of patients, increases patient morbidity (by exposing them to the adverse effects of antibiotics), promotes bacterial resistance, and puts an economic burden on health care [5,8-9]. Thus, it is the need of the hour to practice a rational SAP and minimize the side effects mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…This action is necessary so that the effect between the peak of the medication and the minimum level required for bacterial death is effective. 17 Article VI examined the incidence of redundant antibiotic combinations in US hospitals and identified the existence of high treatment costs associated with combinations in these avoidable patterns. It also found that these combinations contribute to bacterial resistance.…”
Section: Titlementioning
confidence: 99%